Discourse “Concept” Of Medical Personnel (Employee) In Medical Slang - Shukurov Ilkhom Boltayevich; Kamalov Sh.U (Academia One, 2024)
This article discusses issues related to the definition of the concept of “slang” and how it is used in the professional speech of doctors. Medical Slang is an informal subsystem of medical discourse, which has its own stylistic limitations. The article presents many examples of medical slangisms. Doctors use these word- formation models and techniques every day. Whether they are understandable to patients or whether the use of these terms should be limited only to the staff of a medical institution is also mentioned in the article
Keywords: slang; medical slang; slangisms; colloquial term